1994
DOI: 10.1002/1097-0142(19941201)74:11<2889::aid-cncr2820741102>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

The multicentric occurrence of squamous epithelial dysplasia and squamous cell carcinoma in the esophagus

Abstract: Background. The biologic significance of esophageal dysplasia has not yet been completely elucidated, especially regarding the process of multiple occurrences of squamous cell carcinoma. Methods. The multiplicity of dysplasia in 73 patients with solitary carcinoma of the esophagus (Group I) and 21 with multiple carcinomas (Group II)was compared in surgically resected specimens. Results. Thirty‐nine second carcinomas were identified in 13 patients of Group II, and all were superficial. The incidences of five or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 18 publications
4
18
0
1
Order By: Relevance
“…38) In early esophageal cancers, neoplastic cells proliferate in the basal and parabasal compartments of the epithelium, the early stage of which is called dysplasia or carcinoma in situ by pathologists. [40][41][42] Our immunohistochemical study demonstrated that p73 and p21 expressions were conserved in superficially located cancer cells, including early intraepithelial and mucosal cancers and intraepithelial extension. Intraepithelial extension is defined as an intraepithelial carcinoma contiguous to invasive carcinoma, and it coexists in about 30% of squamous cell carcinomas of the esophagus.…”
Section: Discussionmentioning
confidence: 69%
“…38) In early esophageal cancers, neoplastic cells proliferate in the basal and parabasal compartments of the epithelium, the early stage of which is called dysplasia or carcinoma in situ by pathologists. [40][41][42] Our immunohistochemical study demonstrated that p73 and p21 expressions were conserved in superficially located cancer cells, including early intraepithelial and mucosal cancers and intraepithelial extension. Intraepithelial extension is defined as an intraepithelial carcinoma contiguous to invasive carcinoma, and it coexists in about 30% of squamous cell carcinomas of the esophagus.…”
Section: Discussionmentioning
confidence: 69%
“…16 These findings support the concept of field carcinogenesis in the UADT and suggest the presence of common environmental or genetic factors or both associated with the occurrence of cancer.…”
Section: Surgerymentioning
confidence: 99%
“…Conversely, it is generally agreed that esophageal squamous cell carcinoma originates from dysplastic lesions in the esophageal epithelium. Kuwano et al [11][12][13] and others 14,15 repeatedly described a definite relationship between squamous dysplasia and carcinoma in the esophagus, referring to the multicentric occurrence of esophageal carcinomas. As for the malignant potential of dysplastic lesions in the esophagus, no significant differences between squamous dysplasia and carcinoma were demonstrated in DNA ploidy by Itakura et al, 16 nor in cell proliferative activity by Sugimachi et al 17 These findings support the fact that severe dysplasia in the esophagus should be managed as an extremely early cancerous lesion.…”
Section: Discussionmentioning
confidence: 99%